QSGG: query simulation in grammar-compressed graphs - Böttcher, Stefan; Hartel, Rita; Peeters, Sven (Proceedings of The International Workshop on Semantic Big Data)

Pattern Search in Grammar-Compressed Graphs - Böttcher, Stefan; Hartel, Rita; Peeters, Sven (2020 Data Compression Conference (DCC) (Poster))

Approaches for Competetive Routing through Intersections of Hole Abstractions in Hybrid Communication Networks - Skowronek, Michael

Distributed Key Generation for Attribute-Based Signatures - Heimann, Jonas

VR Training for Warehouse Management - Yigitbas, Enes; Jovanovikj, Ivan; Scholand, Janis; Engels, Gregor (Proceedings of the 26th ACM Symposium on Virtual Reality Software and Technology (VRST))

Bildungsdokumentation in KiTa und Grundschule stärkenorientiert gestalten - Büker, Petra; Höke, Julia

Model-based Product Configuration in Augmented Reality Applications - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Augmented Reality (AR) has recently found high attention in mobile shopping apps such as in domains like furniture or decoration. Here, the developers of the apps focus on the positioning of atomic 3D objects in the physical environment. With this focus, they neglect the conﬁguration of multi-faceted 3D object composition according to the user needs and environmental constraints. To tackle these challenges, we present a model-based approach to support AR-assisted product con-ﬁguration based on the concept of Dynamic Software Product Lines. Our approach splits products (e.g. table) into parts (e.g. tabletop, ta-ble legs, funnier) with their 3D objects and additional information (e.g. name, price). The possible products, which can be conﬁgured out of these parts, are stored in a feature model. At runtime, this feature model can be used to conﬁgure 3D object compositions out of the product parts and adapt to user needs and environmental constraints. The beneﬁts of this approach are demonstrated by a case study of conﬁguring modular kitchens with the help of a prototypical mobile-based implementation.
Keywords: Product Configuration; Augmented Reality; Runtime Adaptation; Dynamic Software Product Lines

Run2Survive: A Decision-theoretic Approach to Algorithm Selection based on Survival Analysis - Tornede, Alexander; Wever, Marcel Dominik; Werner, Stefan; Mohr, Felix; Hüllermeier, Eyke (ACML 2020)
Algorithm selection (AS) deals with the automatic selection of an algorithm from a fixed set of candidate algorithms most suitable for a specific instance of an algorithmic problem class, where "suitability" often refers to an algorithm's runtime. Due to possibly extremely long runtimes of candidate algorithms, training data for algorithm selection models is usually generated under time constraints in the sense that not all algorithms are run to completion on all instances. Thus, training data usually comprises censored information, as the true runtime of algorithms timed out remains unknown. However, many standard AS approaches are not able to handle such information in a proper way. On the other side, survival analysis (SA) naturally supports censored data and offers appropriate ways to use such data for learning distributional models of algorithm runtime, as we demonstrate in this work. We leverage such models as a basis of a sophisticated decision-theoretic approach to algorithm selection, which we dub Run2Survive. Moreover, taking advantage of a framework of this kind, we advocate a risk-averse approach to algorithm selection, in which the avoidance of a timeout is given high priority. In an extensive experimental study with the standard benchmark ASlib, our approach is shown to be highly competitive and in many cases even superior to state-of-the-art AS approaches.

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

Local Graph Transformation Primitives For Some Basic Problems In Overlay Networks - Setzer, Alexander

When Donors Turn into Acceptors: Ground and Excited State Properties of FeII Complexes with Amine-Substituted Tridentate Bis-imidazole-2-ylidene Pyridine Ligands - Vukadinovic, Yannik; Burkhardt, Lukas; Päpcke, Ayla; Miletic, Anabel; Fritsch, Lorena; Altenburger, Björn; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)

A Group Signature Scheme from Flexible Public Key Signatures and Structure-Preserving Signatures on Equivalence Classes - Schürmann, Patrick

Enhancing Security by Usage of Universal One-Way Hash Functions - Terfort, Tobias

Algorithmen für selbststabilisierende Skip+-Delaunaygraphen - Guggenmos, Andreas

Strukturoptimierung einer Messradkomponente zur realitätsnäheren Erfassung von Fahrzeuglastdaten und Bruchmechanische Bewertung - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Joy, T.D.; Neumann, J.; Vidner , J.; Kullmer, G.; Richard, H.A. (DVM-Bericht 252, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Einsatz von Topologieoptimierungssoftware - Der Ersatz für den Ingenieur? - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Kullmer, G.; Richard, H.A. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Implementierung additiver Fertigungsverfahren in den chirurgischen Arbeitsablauf - Risse, L.; Kullmer, G. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Digitale mehrseitige Plattformen – Besser verstehen, wie digitale Plattformen funktionieren - Kundisch, Dennis

Influence of Part Microstructure on Mechanicl Properties of PA6X Laser Sintered Specimens - Kummert, Christina; Diekmann, Wolfgang; Tews, Katrin; Schmid, Hans-Joachim (29th Annual International Solid Freeform Fabrication Symposium)

Das Technologiedesign umfassend und strukturiert anpassen - Kundisch, Dennis

Förderung von Kompetenzen im Bereich Wirtschat 4.0 an Fachschulen - Kundisch, Dennis

A new hydrodynamic analogy model for the determination of transport phenomena in random packings - Salten, Alexander Heinrich Johannes; Maćkowiak, Jan F.; Maćkowiak, Jerzy K.; Kenig, Eugeny (Chemical Engineering Science)

Einfluss der Füllkörpergeometrie und Strömungsformen auf die Trennleistung von Absorptionskolonnen - Salten, Alexander Heinrich Johannes; Ehlert, Thomas; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

Entwicklung eines Gitterfüllkörpers ENVIPAC 4 unterstützt durch prädiktive Modellierung - Maćkowiak, J. F.; Maćkowiak, J.; Salten, Alexander Heinrich Johannes; Kenig, Eugeny
Keywords: PubList

Entwicklung modellbasierter Werkzeuge zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny

Numerische Simulation von Gravidestillationsapparaten zur Trennung eines binären Ethanol/Wasser‐Gemisches - Wende, Marc; Philippi, K.; Kenig, Eugeny (Chemie Ingenieur Technik)

Mobile Medien im Schulkontext

Einleitung - Meister, Dorothee; Mindt, Ilka (Mobile Medien im Schulkontext)

Digitale Elemente im Englischunterricht - Mindt, Ilka; Kaymak, Yasemin (Mobile Medien im Schulkontext)

Viele Wege führen nach Rom - Möglichkeiten und Modelle des Inverted-Classroom-Modells aus interdisziplinärer Sicht - Schmidt, Rebekka; Dietrich, Nico; Mindt, Ilka (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Mit digitalen Arbeitsformen das Lernen bereichern: zur Gestaltung sinnstiftender Präsenzphasen mit dem Inverted-Classroom-Modell - Mindt, Ilka; Schmidt, Rebekka; Beißwenger, Michael; Dietrich, Nico (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Student engagement im Inverted Classrom - Mindt, Ilka; Schmidt, Rebekka (Tagungsband zur Tagung Inverted Classroom and beyond 2020)

Kristin Bech and Ruth Möhlig-Falke, eds. Grammar – Discourse – Context: Grammar and Usage in Language Variation and Change. Berlin and Boston, MA: De Gruyter, 2019 - Mindt, Ilka

Beitrag zur Bewertung der funktionalen Sicherheit von Federkraftbremsen - Hübner, Christoph
Federkraftbremsen für industrielle Anwendungen tragen häufig zur Erfüllung einer Sicherheitsfunktion bei. Um Sicherheitsfunktionen zu validieren, sind Sicherheitskennzahlen einzelner Elemente erforderlich. Für Federkraftbremsen werden diese bis dato nur vereinzelt zur Verfügung gestellt. Weiterhin existiert kein Konsens über deren Ermittlung. In dieser Arbeit wird ein bauteilorientierter Ansatz zur Ermittlung von Sicherheitskennzahlen für Federkraftbremsen diskutiert. Unter Berücksichtigung relevanter rechtlich-normativer Rahmenbedingungen wird eine qualitative Zuverlässigkeitsanalyse durchgeführt. Es folgt die simulative und experimentelle Untersuchung einer konkreten Bauteilschadensart. Abschließend wird ein Zuverlässigkeitsblockdiagramm auf Grundlage gewonnener Erkenntnisse hergeleitet.
Keywords: Federkraftbremsen; Funktionale Sicherheit; Technische Zuverlässigkeit; Verschleiß

Entwurf eines Simulationsmodells zur Beurteilung und Beeinflussung des dynamischen Betriebsverhalten von Spindelhubantrieben mit Trapezgewindespindel - Tominski, Johannes
Elektromechanische Spindelhubantriebe werden in einer Vielzahl von unterschiedlichen Anwendungen mit jeweils spezifischen Prozesskennwerten eingesetzt. Dabei kann es vorkommen, dass das dynamische Betriebsverhalten eines Spindelhubantriebs unerwünschte Schwingungen aufweist. Um unerwünschte Betriebszustände bereits vor dem realen Anwendungsfall ersichtlich zu machen, wird im Rahmen dieser Arbeit ein Simulationsmodell von Spindelhubantrieben mit Trapezgewindespindel entwickelt. Dazu wird zunächst recherchiert, welche Schwingungsphänomene in einem Spindelhubantrieb entstehen können. Die Modellbildung wird durch eine Verifikation anhand der identifizierten Schwingphänomene begleitet. Im Anschluss erfolgt eine Validierung des Simulationsmodells durch experimentelle Messungen. Mittels einer Parameterstudie werden Einflussgrößen von zwei Schwingphänomenen analysiert. Die erzielten Erkenntnisse werden anschließend erfolgreich auf ein zuvor schwingungsanfälliges Antriebssystem zugunsten eines stabilen, dynamischen Betriebsverhaltens übertragen, wodurch die Gültigkeit des Modells nachgewiesen wird.

Effect of DNA Origami Nanostructures on hIAPP Aggregation - Hanke, Marcel; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Nanomaterials)
The aggregation of human islet amyloid polypeptide (hIAPP) plays a major role in the pathogenesis of type 2 diabetes mellitus (T2DM), and numerous strategies for controlling hIAPP aggregation have been investigated so far. In particular, several organic and inorganic nanoparticles (NPs) have shown the potential to influence the aggregation of hIAPP and other amyloidogenic proteins and peptides. In addition to conventional NPs, DNA nanostructures are receiving more and more attention from the biomedical field. Therefore, in this work, we investigated the effects of two different DNA origami nanostructures on hIAPP aggregation. To this end, we employed in situ turbidity measurements and ex situ atomic force microscopy (AFM). The turbidity measurements revealed a retarding effect of the DNA nanostructures on hIAPP aggregation, while the AFM results showed the co-aggregation of hIAPP with the DNA origami nanostructures into hybrid peptide–DNA aggregates. We assume that this was caused by strong electrostatic interactions between the negatively charged DNA origami nanostructures and the positively charged peptide. Most intriguingly, the influence of the DNA origami nanostructures on hIAPP aggregation differed from that of genomic double-stranded DNA (dsDNA) and appeared to depend on DNA origami superstructure. DNA origami nanostructures may thus represent a novel route for modulating amyloid aggregation in vivo.

Protein-Assisted Room-Temperature Assembly of Rigid, Immobile Holliday Junctions and Hierarchical DNA Nanostructures - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Kielar, Charlotte; Grundmeier, Guido; Stewart, A. Francis; Keller, Adrian (Molecules)
Immobile Holliday junctions represent not only the most fundamental building block of structural DNA nanotechnology but are also of tremendous importance for the in vitro investigation of genetic recombination and epigenetics. Here, we present a detailed study on the room-temperature assembly of immobile Holliday junctions with the help of the single-strand annealing protein Redβ. Individual DNA single strands are initially coated with protein monomers and subsequently hybridized to form a rigid blunt-ended four-arm junction. We investigate the efficiency of this approach for different DNA/protein ratios, as well as for different DNA sequence lengths. Furthermore, we also evaluate the potential of Redβ to anneal sticky-end modified Holliday junctions into hierarchical assemblies. We demonstrate the Redβ-mediated annealing of Holliday junction dimers, multimers, and extended networks several microns in size. While these hybrid DNA–protein nanostructures may find applications in the crystallization of DNA–protein complexes, our work shows the great potential of Redβ to aid in the synthesis of functional DNA nanostructures under mild reaction conditions.

Self-assembly of highly ordered DNA origami lattices at solid-liquid interfaces by controlling cation binding and exchange - Xin, Yang; Martinez Rivadeneira, Salvador; Grundmeier, Guido; Castro, Mario; Keller, Adrian (Nano Research)
Abstract The surface-assisted hierarchical self-assembly of DNA origami lattices represents a versatile and straightforward method for the organization of functional nanoscale objects such as proteins and nanoparticles. Here, we demonstrate that controlling the binding and exchange of different monovalent and divalent cation species at the DNA-mica interface enables the self-assembly of highly ordered DNA origami lattices on mica surfaces. The development of lattice quality and order is quantified by a detailed topological analysis of high-speed atomic force microscopy (HS-AFM) images. We find that lattice formation and quality strongly depend on the monovalent cation species. Na + is more effective than Li + and K + in facilitating the assembly of high-quality DNA origami lattices, because it is replacing the divalent cations at their binding sites in the DNA backbone more efficiently. With regard to divalent cations, Ca 2+ can be displaced more easily from the backbone phosphates than Mg 2+ and is thus superior in guiding lattice assembly. By independently adjusting incubation time, DNA origami concentration, and cation species, we thus obtain a highly ordered DNA origami lattice with an unprecedented normalized correlation length of 8.2. Beyond the correlation length, we use computer vision algorithms to compute the time course of different topological observables that, overall, demonstrate that replacing MgCl 2 by CaCl 2 enables the synthesis of DNA origami lattices with drastically increased lattice order.

Quantitative Assessment of Tip Effects in Single‐Molecule High‐Speed Atomic Force Microscopy Using DNA Origami Substrates - Kielar, Charlotte; Zhu, Siqi; Grundmeier, Guido; Keller, Adrian (Angewandte Chemie International Edition)

Dynamics of lattice defects in mixed DNA origami monolayers - Xin, Yang; Ji, Xueyin; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami lattice formation at solid–liquid interfaces is surprisingly resilient toward the incorporation of DNA origami impurities with different shapes.

Cryopreservation of DNA Origami Nanostructures - Xin, Yang; Kielar, Charlotte; Zhu, Siqi; Sikeler, Christoph; Xu, Xiaodan; Möser, Christin; Grundmeier, Guido; Liedl, Tim; Heuer‐Jungemann, Amelie; Smith, David M.; Keller, Adrian (Small)

Challenges and Perspectives of DNA Nanostructures in Biomedicine - Keller, Adrian; Linko, Veikko (Angewandte Chemie International Edition)

Amyloid aggregation at solid-liquid interfaces: Perspectives of studies using model surfaces - Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Arranging Small Molecules with Subnanometer Precision on DNA Origami Substrates for the Single‐Molecule Investigation of Protein–Ligand Interactions - Huang, Jingyuan; Suma, Antonio; Cui, Meiying; Grundmeier, Guido; Carnevale, Vincenzo; Zhang, Yixin; Kielar, Charlotte; Keller, Adrian (Small Structures)

Molecular adhesion science and engineering of nanostructured poly(acrylic acid)/metal oxide interfaces - Meinderink, Dennis
Das grundlegende Verständnis von makroskopischen Haftungsphänomenen beginnt bei der Analyse von molekularen Wechselwirkungen unter kontrollierten Bedingungen (Materialeigenschaften, chemische Oberflächenzusammensetzung, und weiteren Einflussfaktoren wie z.B. pH-Wert, Elektrolytzusammensetzung). In dieser Arbeit wurden die molekularen und makroskopischen Haftungseigenschaften von makromolekularer Poly(acrylsäure) (PAA) als potenzieller Haftungsvermittler auf Edelstahl und verschiedenen nanostrukturierten Zinkoxid (ZnO) Oberflächen untersucht, die mittels elektrochemischer und hydrothermalen Abscheidemethoden auf Edelstahl und feuerverzinktem Stahl (HDG) abgeschieden wurden. Molekulare Haftungsmechanismen zwischen PAA und ZnO basierend auf multi-koordinativen Bindungen in Abhängigkeit von der Oberflächenchemie und der Verweilzeit konnten mit der s.g. Einzelmolekülspektroskopie aufgeklärt werden. Die Ergebnisse aus weiteren makroskopischen Enthaftungsexperimenten und Rückseitenanalytik bei der Verwendung von verdünnten, wässrigen PAA-Lösungen zur Vorbehandlung von nanostrukturierten ZnO Filmen auf HDG Stahl untermauerten die starken Wechselwirkungen zwischen ZnO-PAA. Mittels Elektropolymerisation abgeschiedene PAA Filme zeigten eine signifikante Steigerung in den makroskopischen Haftungseigenschaften bei einem ausgewählten Model-Epoxid-Amin-Klebstoff auf Edelstahl. Die Kombination von ZnO Tetrapoden (ZnO TP) und PAA als hybridische, haftungsverbessernde Sprühbeschichtungen aus wässrigen Dispersionen auf Poly(propylen) Folien bestätigten, sowohl die chemischen, als auch mechanischen Haftungseigenschaften von nanostrukturierten ZnO/PAA Interphasen. Daher können PAA/Metalloxid-Grenzflächen die Tür in diversen technischen Ansätzen für innovative Anwendungen öffnen, wie z.B. in Sprühapplikationstechniken.

Spray pyrolysis of thin adhesion-promoting ZnO films on ZnMgAl coated steel - Grothe, R.; Knust, S.; Meinderink, Dennis; Voigt, M.; Orive, A. González; Grundmeier, Guido (Surface and Coatings Technology)

Waveguide resonator with an integrated phase modulator for second harmonic generation - Stefszky, Michael; Santandrea, Matteo; vom Bruch, Felix; Krapick, S.; Eigner, Christof; Ricken, R.; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Investigation of the frequency dependent spatio-temporal dynamics and controllability of microdischarges in unipolar pulsed plasma electrolytic oxidation - Hermanns, Patrick; Boeddeker, Simon; Bracht, Vera; Bibinov, Nikita; Grundmeier, Guido; Awakowicz, Peter (Journal of Physics D: Applied Physics)

Investigation of the frequency dependent spatio-temporal dynamics and controllability of microdischarges in unipolar pulsed plasma electrolytic oxidation - Hermanns, Patrick; Boeddeker, Simon; Bracht, Vera; Bibinov, Nikita; Grundmeier, Guido; Awakowicz, Peter (Journal of Physics D: Applied Physics)

Multilayer coatings based on the combination of perfluorinated organosilanes and nickel films for injection moulding tools - Calderón, Juan Carlos; Koch, Leon; Bandl, Christine; Kern, Wolfgang; Jilg, Jannik; Schilp, Catharina; Moritzer, Elmar; Grundmeier, Guido (Surface and Coatings Technology)

Kinetic studies of cathode degradation as caused by ice formation in MEAs - Liphardt, L.; Disson, S.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)

Investigation of the passive layer on a solid-state sintered silicon carbide ceramic formed in sulfuric acid - Schneider, M.; Kremmer, K.; Voigt, M.; Grundmeier, Guido (Corrosion Science)

Design and Objective Evaluation of Filter- and Optimization-based Motion Cueing Strategies for a Hybrid Kinematics Driving Simulator with 5 Degrees of Freedom - Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (International Journal On Advances in Systems and Measurements)

Design and Evaluation of a Novel Filter-Based Motion Cueing Strategy for a Hybrid Kinematics Driving Simulator with 5 Degrees of Freedom - Biemelt, Patrick; Mertin, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR)

Macroscopic Traffic Flow Control using Consensus Algorithms - Mertin, Sven; Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (The 23rd IEEE International Conference on Intelligent Transportation Systems)

Real-Time Optimized Model Predictive Control of an Active Roll Stabilization System with Actuator Limitations - Nareyko, Georgi; Biemelt, Patrick; Trächtler, Ansgar (Proceedings of the 21st IFAC World Congress)

A Model-Based Online Reference Prediction Strategy for Model Predictive Motion Cueing Algorithms - Biemelt, Patrick; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 21st IFAC World Congress)

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Mechanismen auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Entwurf komplexer Automatisierungssysteme (EKA))

Language-agnostic Injection Detection - Hermerschmidt, Lars; Straub, Andreas; Piskachev, Goran (2020 IEEE Security and Privacy Workshops (SPW))

SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE))

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Wood-based materials as a sustainable alternative for future car body construction - Schweizer, Swetlana; Akbulut Irmak, Emine Fulya; Tröster, Thomas

Two-dimensional electron bound hole photoluminescence in GaAs in perpendicular magnetic fields - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Strain-driven InAs island growth on top of GaAs(111) nanopillars - Riedl, T.; Kunnathully, V. S.; Trapp, A.; Langer, T.; Reuter, Dirk; Lindner, J. K. N. (Physical Review Materials)

Kernel-Based Approximation of the Koopman Generator and Schrödinger Operator - Klus, Stefan; Nüske, Feliks; Hamzi, Boumediene (Entropy)
Many dimensionality and model reduction techniques rely on estimating dominant eigenfunctions of associated dynamical operators from data. Important examples include the Koopman operator and its generator, but also the Schrödinger operator. We propose a kernel-based method for the approximation of differential operators in reproducing kernel Hilbert spaces and show how eigenfunctions can be estimated by solving auxiliary matrix eigenvalue problems. The resulting algorithms are applied to molecular dynamics and quantum chemistry examples. Furthermore, we exploit that, under certain conditions, the Schrödinger operator can be transformed into a Kolmogorov backward operator corresponding to a drift-diffusion process and vice versa. This allows us to apply methods developed for the analysis of high-dimensional stochastic differential equations to quantum mechanical systems.

Posthuman Dystopia: Animal Surrealism and Permanent Crisis in Contemporary British Theatre - Tönnies, Merle; Voigts, Eckart (Journal of Contemporary Drama in English)

Bilingual education in monolingual contexts: a comparative perspective - Rumlich, Dominik (The Language Learning Journal)

Englischsprachige Jugendbücher innerhalb und außerhalb des Englischunterrichts – Young Adult Fiction als empirischer Gegenstand der Literaturdidaktik - Matz, Frauke; Rumlich, Dominik (KONTROVERS. Literaturdidaktik meets Literaturwissenschaft)

Die mündliche Prüfung in der Sekundarstufe II: Herausforderung und Chance für die Fremdsprachendidaktik - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Testen bildungssprachlicher Kompetenzen und akademischer Sprachkompetenzen – Zugänge für Schule und Hochschule)

Softwareentwicklung wie am Fliessband - Koch, Thorsten; Meyer, Matthias; Fazal-Baqaie, Masud; Runschke, Hubert (Software Engineering 2020 (SE 2020))

Entwurf eines Simulationsmodells zur Bewertung des Betriebsverhaltens von elektromechanischen Spindelhubantrieben - Tominski, J.; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)
Simulationsmethoden bieten die Möglichkeit, instabile Betriebszustände von Antriebssystemen noch vor dem Einsatz in einer realen Anwendung zu identifizieren und gezielt Gegenmaßnahmen abzuleiten. In dem vorliegenden Artikel wird die Entwicklung eines Simulationsmodells für elektro- mechanische Spindelhubantriebe beschrieben. Im Fokus der Betrachtung stehen insbesondere reibungsinduzierte Schwingphänomene, die in Schneckengetrieben und Trapezgewindespindeln entstehen können. Das Simulationsmodell wird anhand von experimentellen Messungen für mehrere stabile Betriebspunkte und für einen instabilen Betriebszustand validiert. Eine Diskussion der Ergebnisse schließt den Beitrag ab.

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, G.; Zrenner, A. (Journal of Applied Physics)

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, Gerhard; Zrenner, Artur (Journal of Applied Physics)

Software tools for business model innovation: Current state and future challenges - Szopinski, Daniel; Schoormann, T.; John, Thomas; Knackstedt, R.; Kundisch, Dennis (Electronic Markets)

Ancillary market signaling: A two-stage model of economic reputation on ancillary market success - Kaimann, Daniel (Applied Economics Letters)

Extractive Snippet Generation for Arguments - Alshomary, Milad; Düsterhus, Nick; Wachsmuth, Henning (Proceedings of 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval)

Transient Bodies in Anglophone Literature and Culture

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance. - Lehmann, T; Büchel, D; Cockcroft, J; Louw, Q; Baumeister, Jochen (Neuroscience)

Electrocortical dynamics differentiate athletes exhibiting low- and high- ACL injury risk biomechanics. - Bonnette, S; Diekfuss, JA; Grooms, DR; Kiefer, AW; Riley, MA; Riehm, C; Moore, C; Barber Foss, KD; DiCesare, CA; Baumeister, Jochen; Myer, GD (Psychophysiology)

Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.

Privacy-Preserving Incentive Systems with Highly Efficient Point-Collection - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Slamanig, Daniel; Striecks, Christoph (Proceedings of the 15th ACM Asia Conference on Computer and Communications Security (ASIA CCS ’20),)

Inwiefern können Praxisphasen im Studium zu einer Theorie-Praxis-Relationierung beitragen? Implikationen für die professionelle Entwicklung angehender Lehrkräfte. - Harteis, Christian; Caruso, Carina (Verlängerte Praxisphasen in der universitären Lehrerbildung: Spannungsfelder zwischen Theorie, Praxis und der Bestimmung von Professionalisierung)

Challenges in Model-Driven Development of Multi-Platform Augmented Reality Applications - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 22st Workshop Software-Reengineering & Evolution (WSRE) & 11h Workshop Design for Future (DFF))

Higher Income, Larger Loan? Monotonicity Testing of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (Proceedings of the ACM SIGSOFT International Symposium on Software Testing and Analysis (ISSTA).)

Algorithm Selection for Software Validation Based on Graph Kernels - Richter, Cedric; Hüllermeier, Eyke; Jakobs, Marie-Christine; Wehrheim, Heike (Journal of Automated Software Engineering)

Dynamic Provisioning of Network Services on Heterogeneous Resources - Razzaghi Kouchaksaraei, Hadi; Shivarpatna Venkatesh, Ashwin Prasad; Churi, Amey; Illian, Marvin; Karl, Holger (European Conference on Networks and Communications (EUCNC 2020))

Designing Digital Community Service Platforms for Crowd-Based Services in Urban Areas - Bartelheimer, Christian; Wolf, Verena; Langhorst, Nico; Seegers, Florian (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology)

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)

PS³—A Domain-specific Modeling Language for Platform-based Smart Service Systems - Lüttenberg, Hedda (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry. DESRIST 2020)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Density and Thermodynamic Speed of Sound of Liquid Vinyl Chloride - Javed, Muhammad Ali; Rüther, Moritz; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

What Are We Talking About When We Talk About Technology Pivots? – A Delphi Study - Bohn, Nicolai; Kundisch, Dennis (Information & Management)

The Shanghai-Hong Kong Stock Connect: An Application of the Semi-CGARCH and Semi-EGARCH - Peitz, Christian; Feng, Yuanhua; Gilroy, Bernard Michael; Stöckmann, Nico (Asian Economic and Financial Review)

Die Niedrigzinspolitik der Europäischen Zentralbank - Gilroy, Bernard Michael; Peitz, Christian (WISU – Das Wirtschaftsstudium)

Survey on Algorithms for Self-Stabilizing Overlay Networks - Feldmann, Michael; Scheideler, Christian; Schmid, Stefan (ACM Computing Surveys)
The maintenance of efficient and robust overlay networks is one of the most fundamental and reoccurring themes in networking. This paper presents a survey of state-of-the-art algorithms to design and repair overlay networks in a distributed manner. In particular, we discuss basic algorithmic primitives to preserve connectivity, review algorithms for the fundamental problem of graph linearization, and then survey self-stabilizing algorithms for metric and scalable topologies. We also identify open problems and avenues for future research.

Time- and Space-Optimal Discrete Clock Synchronization in the Beeping Model - Feldmann, Michael; Khazraei, Ardalan; Scheideler, Christian (Proceedings of the 32nd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We consider the clock synchronization problem in the (discrete) beeping model: Given a network of $n$ nodes with each node having a clock value $δ(v) \in \{0,… T-1\}$, the goal is to synchronize the clock values of all nodes such that they have the same value in any round. As is standard in clock synchronization, we assume arbitrary activations for all nodes, i.e., the nodes start their protocol at an arbitrary round (not limited to $\{0,…,T-1\}$). We give an asymptotically optimal algorithm that runs in $4D + \Bigl\lfloor \frac{D}{\lfloor T/4 \rfloor} \Bigr \rfloor · (T \mod 4) = O(D)$ rounds, where $D$ is the diameter of the network. Once all nodes are in sync, they beep at the same round every $T$ rounds. The algorithm drastically improves on the $O(T D)$-bound of \cite{firefly_sync} (where $T$ is required to be at least $4n$, so the bound is no better than $O(nD)$). Our algorithm is very simple as nodes only have to maintain $3$ bits in addition to the $\lceil \log T \rceil$ bits needed to maintain the clock. Furthermore we investigate the complexity of self-stabilizing solutions for the clock synchronization problem: We first show lower bounds of $Ω(\max\{T,n\})$ rounds on the runtime and $Ω(\log(\max\{T,n\}))$ bits of memory required for any such protocol. Afterwards we present a protocol that runs in $O(\max\{T,n\})$ rounds using at most $O(\log(\max\{T,n\}))$ bits at each node, which is asymptotically optimal with regards to both, runtime and memory requirements.

Mechanisms, Preferences, and Heterogeneity in Matching Markets - Stroh-Maraun, Nadja

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)

Hypothesis-driven Adaptation of Business Models based on Product Line Engineering - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Proceedings of the 22nd IEEE International Conference on Business Informatics)
The continuous innovation of its business models is an important task for a company to stay competitive. During this process, the company has to validate various hypotheses about its business models by adapting to uncertain and changing customer needs effectively and efficiently. This adaptation, in turn, can be supported by the concept of Software Product Lines (SPLs). SPLs reduce the time to market by deriving products for customers with changing requirements using a common set of features, structured as a feature model. Analogously, we support the process of business model adaptation by applying the engineering process of SPLs to the structure of the Business Model Canvas (BMC). We call this concept a Business Model Decision Line (BMDL). The BMDL matches business domain knowledge in the form of a feature model with customer needs to derive hypotheses about the business model together with experiments for validation. Our approach is effective by providing a comprehensive overview of possible business model adaptations and efficient by reusing experiments for different hypotheses. We implement our approach in a tool and illustrate the usefulness with an example of developing business models for a mobile application.
Keywords: Business Model Decision Line; Business Model Adaptation; Hypothesis-driven Adaptation; Software Product Line; Feature Model

Model-based Hypothesis Engineering for Supporting Adaptation to Uncertain Customer Needs - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Business Modeling and Software Design)
To build successful products, the developers have to adapt their product features and business models to uncertain customer needs. This adaptation is part of the research discipline of Hypotheses Engineering (HE) where customer needs can be seen as hypotheses that need to be tested iteratively by conducting experiments together with the customer. So far, modeling support and associated traceability of this iterative process are missing. Both, in turn, are important to document the adaptation to the customer needs and identify experiments that provide most evidence to the customer needs. To target this issue, we introduce a model-based HE approach with a twofold contribution: First, we develop a modeling language that models hypotheses and experiments as interrelated hierarchies together with a mapping between them. While the hypotheses are labeled with a score level of their current evidence, the experiments are labeled with a score level of maximum evidence that can be achieved during conduction. Second, we provide an iterative process to determine experiments that offer the most evidence improvement to the modeled hypotheses. We illustrate the usefulness of the approach with an example of testing the business model of a mobile application.
Keywords: Hypothesis Engineering; Model-based; Customer Need Adaptation; Business Model; Product Features